Assessing the Impact of Federalism on Constitutional Compliance - Jaroslaw Kantorowicz; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2024)
Federalism is a constitutionalized version of multi-tier governance. Proponents of veto-player theory argue that a high number of veto players leads to a high degree of policy stability. Compared to states with a unitary structure, federal countries, in which at least one sub-central level of government is constitutionally recognized and endowed with some degree of exclusive competences, dispose of a higher number of veto players, who can voice and challenge constitutional non-compliance by the central government. In this paper, we therefore ask whether federally constituted states also enjoy a higher degree of constitutional compliance, i.e. have governments that respect and enforce the promises made in their country's constitution. At the same time, with a higher number of governments under federalism, there are more chances that some of them will not comply with constitutional constraints leading to greater non-compliance. To test these hypotheses, we employ data from up to 162 countries and apply standard panel data estimation techniques. Contrary to expectations, our results indicate that federalism is neither positively nor negatively correlated with constitutional compliance of the respective countries.
Keywords: H11; K10; K42; P48; Z10; Z18; 330; constitutional compliance; de jure-de facto gap; federalism